Developing and Promoting a Cultural and Historical Tour Package along the Central Vietnam Heritage Route at BenThanh Tourist - Nguyen, Thanh Phong (Vietnam-Korea University of Information and Communication Technology, 2025)
Bachelor thesis of Business Administration - Major in Digital Travel and Tourism Services Management